PENYUSUNAN ROADMAP REFORMASI BIROKRASI DALAM MEWUJUDKAN GOOD GOVERNANCE DI KOTA BANDUNG - Kurniasih, Dewi; Amin, Mohammad Ali Syamsudin; Karniawati, Nia (Jurnal Transformative, 2017)
Bureaucracy reform is an important thing. The aim is to actualize good governance, particularly in Bandung city. The research is started with continuing previous program, program socialization, recommended evaluation or progress of bureaucracy reform, arrangement of reformation agenda in 2015-2019, implementation of regulation, gradual report related with progress of bureaucracy reform program in Bandung city. Bureaucracy reform is implemented in purpose to actualize increasing of public service quality towards society. The government has issued many regulations as legal and operational directions in implementation of bureaucracy reform in period 2015-2019. The research has special target for helping local government, Bandung City in arranging road map of bureaucracy reform in Bandung City in second period, based on National Medium-Term Development Plan (RPJMN). With this special target, increasing of public service quality by Bandung bureaucracy will be reached.